Studi Komparasi Karakteristik Asap Cair Hasil Pirolisis dari Kulit Durian, Pelepah dan Tandan Kosong Sawit dengan Pemurnian Secara Distilasi (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2014)
Liquid  smoke  is  one  of  the  modern  methods  of  food  preservation.  It  made  from biomass containing cellulose, hemicellulose and  lignin. The purpose of  this research was  to generate and  compare  the  characteristics of  liquid  smoke  results  from  pyrolysis    feedstock durian shell, EFB and palm midrib and distillation refining. The method is carried out every feedstock  in  the pyrolysis  temperature  range of 300-350  °C and distilled  temperature at of 175  °C.  Then,  performed  analysis  of  the  characteristics  of  liquid  smoke  compounds  using GC/MS  and  test  pH  using  a  pH meter. The  yield  of  liquid  smoke  pyrolysis  results  of  each feedstock  is  durian  shell  42.474%;  49.647%  EFB  and  palm  midrib  44.66%.  From  the analysis of GC/MS, acetic acid has the highest percent area among 16 dominant compounds in  liquid  smoke  of  pyrolysis  results  and  among  14  dominant  compounds  after  distillation. Percent acetic acid in the area of liquid smoke each feedstock pyrolysis results changed after the distillation of durian  shell 54.17%  to 62.8%; EFB 48.83%  to 74.39% and palm midrib 52.19%    to 41.14%. The percent area of phenolic compounds  that act as antioxidants  skin durian  is  1.38%  to  2.72%; EFB  5.28%  to  6.56%  ;  palm midrib  9.12 %  to  5.84 %. Liquid smoke pH values obtained after distillation is  the durian shell 3.8; EFB 3.5 and 3.4 of palm midrib . Keywords :, durian shell, EFB, liquid Smoke, palm  midrib, pyrolysis